Thromboembolic complications after an ankle joint open fracture in a patient with a history of deep vein thrombosis in the lower limbs - Stankowski, Tomasz; Aboul-Hassan, Sleiman Sebastian; Stępiński, Piotr; Szymańska, Anna; Marczak, Jakub; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
A 55-year-old patient was admitted to the Department of Orthopedics due to an open fracture in the right ankle joint. On the seventh day of hospitalization the patient experienced a transient ischemic attack. During the next day, dyspnea, chest pain and a ‘rider’ type pulmonary embolism in the pulmonary trunk occluding both pulmonary arteries and its branches were diagnosed. The patient was transferred to the Department of Cardiac Surgery. He underwent pulmonary embolectomy for massive pulmonary, right and left atrial embolism, and left ventricular embolism. ASD II was closed during this procedure. Ultrasonography with Doppler was performed 6 days after the surgery and revealed deep vein thrombosis, so the patient was transferred to the Department of Vascular Surgery for temporary inferior vena cava filter placement at the time of orthopedic surgery. The next day after implantation of the filter, the lower limb was operated on, and 14 days after orthopedic surgery, the vena cava filter was removed.